Analysis of The Application of Ultraviolet Water Sterilizer in Maintaining The Quality of Drinking Water on The MV. EPIC PAN - Muhamad Fitra, Laode; Almuzani, Nafi; Simanjuntak, Marihot (Green Publisher, 2023)
Ultraviolet water sterilizer is a long cylindrical device used for the sterilization of water into drinkable water. Ultraviolet water sterilizer has two main parts: an adapter and UV tubes. The adapter serves to drain the ratio of electricity according to the voltage and current required by ultraviolet water sterilizer. UV tubes contain ultraviolet lamps where light is the main equipment for making the water drinkable and the water will flow along with the ultraviolet rays, so that the water flowing in the tube is passed through the sterilization process with ultraviolet rays so that the water is unfit for consumption. The problems that the authors take in this study are the factors that affect the declining quality of sterilization, the impact of what happens when the quality of sterilization decreases, and what efforts are made to keep the quality of sterilization is not decreased. The data was collected through observations, interviews, and literature directly related to the subject related to the factors, the impact, as well as the efforts of the decline in the sterilization process to the sterilizer in order to improve the quality of drinking water. The cause of the decline to the sterilization process in order to improve the quality of drinking water in MV. PAN EPIC that dirty filters, dirty water tubes, and the dirty ultraviolet lamp or resulting in less fresh water, complaints against the company, as well as the ship's operational costs are reduced. Therefore some efforts are made to improve the quality of the results of sterilization including cleaning filters, cleaning water tubes, and also cleaning the germicidal lamp,